1975
DOI: 10.1038/bjc.1975.26
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of oesophageal carcinoma in the Transkei, South Africa

Abstract: Summary.-Data on the incidence of cancer of the oesophagus in the Transkei for years 1965-69 are presented, age specific rates for the sexes discussed and the spatial relationship of well-defined regions of high and low incidence demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…2 with raised crude rates for these 2 areas. These findings underline the high levels of oesophageal cancer known to obtain in the Transkei (Burrell, 1957;Rose, 1969) and the raised levels in the Natal African (Schonland and Bradshaw, 1968) and in the Johannesburg African (Robertson, Harington and Bradshaw, 1971b;Warwick and Harington, 1973). …”
Section: Spatial Analysismentioning
confidence: 63%
See 1 more Smart Citation
“…2 with raised crude rates for these 2 areas. These findings underline the high levels of oesophageal cancer known to obtain in the Transkei (Burrell, 1957;Rose, 1969) and the raised levels in the Natal African (Schonland and Bradshaw, 1968) and in the Johannesburg African (Robertson, Harington and Bradshaw, 1971b;Warwick and Harington, 1973). …”
Section: Spatial Analysismentioning
confidence: 63%
“…3 for these localities). This work among the absentee miners from the Transkei has been reinforced by a very similar incidence gradient found among both males and females, separately and together, for confirmed cases of oesophageal cancer in the general resident population of the Transkei itself (Rose and McGlashan, 1975 (von Zeynek, 1973;McGlashan, 1974). Further recording and statistical analyses should assist the search for local environmental factors injurious to the Xhosa speaking peoples, both north and south of the Kei River.…”
Section: Spatial Analysismentioning
confidence: 87%
“…Areas in the Transkei that are only 150 km apart have esophageal cancer incidences that differ 2-to 3-fold (14,15). Cytologic analysis of esophageal scrapings from patients in these areas showed that cytologically abnormal esophageal mucosal cells were present in patients from the high-risk area (16).…”
mentioning
confidence: 99%
“…Colorectal cancer (ICD 9,(153)(154) This cancer is of low incidence generally even though there has been an increase in the pooled CIR from 0.9 in 1964 -79 to 2.3 in (Figure 3) follows the earlier mapping (Rose and McGlashan, 1975 1989 -96 (Po0.01). It is especially low in Transkei, with an ASIR of 49, and has risen in Mozambique (from CIR 0.6 to 2.9 (Po0.01) ( Table 5).…”
Section: Spatial and Temporal Distribution Of Cancer Sitesmentioning
confidence: 96%
“…Over the years, this site of cancer has been recognised as one of the major health problems of Transkei, both from studies of the gold miners and of men and women resident in the territory Cancer incidence in black gold miners in South Africa ND McGlashan et al (Rose and McGlashan, 1975). From its geographical distribution, it has been firmly associated with Xhosa customary usage of alcohol and homegrown and commercial tobacco, although there seems little doubt that the use of pipe tobacco in various forms is the principal determinant (Bradshaw et al, 1983).…”
Section: Spatial and Temporal Distribution Of Cancer Sitesmentioning
confidence: 99%